Defining Levels of Learning for Strengths Development Programs in Pharmacy - Kristin K. Janke, Ph.D; Todd D. Sorensen, Pharm.D; Andrew P. Traynor, Pharm.D., BCPS (University of Minnesota Libraries Publishing, 2010)
The Clifton StrengthsFinder® is an online measure of personal talent that identifies where an individual's greatest potential for building strengths exists. This paper describes a framework for strengths education in pharmacy which includes introductory, intermediate and advanced levels of learning. The use of the StrengthsFinder® assessment and supporting workshops aids student pharmacists, pharmacy residents and practitioners in identifying and refining their talents and connecting talents to roles in the profession. Additional learning strategies support a learner's progression to intermediate and advanced levels of learning, which focus on the application of strengths in teams, leadership, and organizational development. By articulating and recognizing levels of learning around strengths-related content and skills, strong instructional design is fostered. Optimal design includes development of a sequence of learning opportunities delivered over time, a roll-out plan and consideration of the instructional resources required.